(untitled) (Journal of the College of Basic Education, 2023)
If he does any good deed; Or a thought, whether divine or human, is like a biography or a remembrance through a discontinuity nowIn their belief that it is thanks to him in changing aspects of their lives, the philosophers of history have seen some of them as history is notExcept for the biography of the great men, although the writers said: It is a literary art in which the writer or author narrates a lifeA historical figure or a group of people who were characterized by satisfactory features for all, which they called (the biography).historical) or if he wanted to talk about himself, they called it (the self-discipline)» and each type of awareness has goalsI was about to say about it, although the second type depends on the one who writes or writes of his own free will or on a bank.And it is not an easy or easy matter, because no one can write or write it down except for those who are trained in the ability of the historian.his sophistication; And the sense and feeling of the writer, as it is the story of a distinguished person who may have features that are not in meOther than him, so first of all, among Muslims, it was launched on what is written down from the life of the Messenger Muhammad (may God bless him and grant him peace).And his family and peace) and if he did not write it down in his daily behavior »and his conquests that Baha carried out and what was the drawing of plans inAspects of its organization of the emerging state in its Quranic thought; and the types of siege that accompanied it; and distribution of the shade